Insights into PCDD/Fs and PAHs in biomass boilers envisaging risks of ash use as fertilizers - Lopes, Helena (2020)
ABSTRACT: Since ashes are a possible source of Persistent Organic Pollutants (POPs) contamination, their application in soils must be subject to more study and control. In this scope, feed residual forest biomasses and biomass ashes, collected along one year in four biomass power stations, were characterized mainly for their polychlorinated dibenzo-p-dioxins and polychlorinated dibenzofurans (PCDD/Fs) and Polycyclic Aromatic Hydrocarbons (PAHs) contents. The biomasses present concerning levels of Cl (0.04-0.28%) that may lead to PCDD/Fs formation. The biomasses also contain OCDD (29-260 ng/kg) and 1,2,3,4,6,7,8-HpCDD (35 ng/kg) that may contribute to increased Toxic Equivalents (TEQs) of ashes, possibly involving dechlorination and ash enrichment mechanisms. While the WHO2005-TEQs in bottom ashes (14-20 ng TEQ/kg) reaches the proposed limit (20 ng TEQ/kg) for ash use as fertilizers, in fly ashes (35-1139 ng TEQ/kg) the limit is exceeded. PAHs are below 0.02 mg/kg in bottom ashes and 1.5-2.5 mg/kg in fly ashes, complying with the proposed limit of 6 mg/kg. As bottom and fly ash streams may contain different ash flows, a clear definition of ash mixes is required. Correlations between unburned carbon (C), PAHs and PCDD/Fs were not found, which highlights the need for compulsory PCDD/Fs analysis in ashes, independently of their origin, burnout degree or levels of other contaminants. A sensitivity analysis was performed to evaluate the impact of handling non-detected values, which showed more impact for TEQs values close to the proposed regulatory limit of PCDD/Fs. These findings highlight the need to define reporting protocols of analytical results for risk assessments and conformity evaluation.